Mechanical efficiency during repetitive vertical jumping - McCaulley, G. O.; Cormie, P.; Cavill, M. J.; Nuzzo, J. L.; Urbiztondo, Z. G.; McBride, J. M. (European Journal of Applied Physiology, 2007)
The purpose of this study was to compare mechanical efficiency between repeated static jumps (SJ), countermovement jumps (CMJ), drop jumps from 75% of maximum CMJ jump height (75DJ) and drop jumps from 125% of maximum CMJ height (125DJ). Subjects included eight jump-trained males. All subjects completed 30 continuous repetitions in the SJ, CMJ, 75DJ, and 125DJ. Oxygen consumption, peak force and center of mass displacement for each repetition during the four jumping patterns were measured. ME was calculated from a combination of force-time curves, displacement-time curves and lactate-corrected oxygen consumption values. In addition, muscle activity was recorded from the vastus medialis, vastus lateralis and biceps femoris using surface electromyography (EMG). 125DJ and 75DJ resulted in significantly (P = 0.05) greater ME in comparison to CMJ and SJ. CMJ resulted in significantly greater ME in comparison to SJ. In addition, braking phase muscle activity was significantly greater in 125DJ and 75DJ in comparison to CMJ. Negative work was significantly different between 125DJ, 75DJ and CMJ (125DJ > 75DJ > CMJ). There was a significant positive correlation (r = 0.68) between ME and negative work performed across 125DJ, 75DJ and CMJ. These findings suggest that stretch-shortening cycle movements, which include a strenuous braking phase combined with simultaneous high muscle activity, increase ME. This may be due to optimal muscle-tendon unit kinetics and usage of stored elastic energy.